2009
DOI: 10.1002/chem.200900477
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Enhanced Diastereo‐ and Regioselectivity in the PdII‐Catalyzed Synthesis of Six‐ and Eight‐Membered Heterocycles via cis‐Aminopalladation

Abstract: The Pd(II)-catalyzed intramolecular oxidative cyclization of tosyl-protected cis- and trans-N-allyl-2-aminocyclohexanecarboxamides was examined, and efficient syntheses of cyclohexane-fused pyrimidin-4-ones and 1,5-diazocin-6-ones were developed. In the course of the research, a marked solvent effect was observed on both the regio- and diastereoselectivity. Additionally, a novel Pd(II)-mediated domino oxidation, oxidative amination reaction was discovered. Our experimental and theoretical findings suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Puzzled by the forbidden (or strongly inhibited) elimination of the cyclic N u PI proxicyclic β-H atoms, we decided to undertake further studies on this issue . In the particular case of N -Ts carbamates and N -Ts carboxamides, we thought that under the acidic reaction conditions the nitrogen atom of the cyclic A m PI is likely to be protonated which would, in turn, inhibit dehydropalladation, the proxicyclic hydrogen atom being too electron-depleted to interact with the palladium atom.…”
mentioning
confidence: 99%
“…Puzzled by the forbidden (or strongly inhibited) elimination of the cyclic N u PI proxicyclic β-H atoms, we decided to undertake further studies on this issue . In the particular case of N -Ts carbamates and N -Ts carboxamides, we thought that under the acidic reaction conditions the nitrogen atom of the cyclic A m PI is likely to be protonated which would, in turn, inhibit dehydropalladation, the proxicyclic hydrogen atom being too electron-depleted to interact with the palladium atom.…”
mentioning
confidence: 99%
“…A separate isomerization step was therefore conducted with carbonylchlorohydridotris(triphenylphosphine)ruthenium(II) , in toluene under reflux for 24 h to afford macrocycle 1 in good yield over two steps. To the best of our knowledge, this reaction constitutes the first reported isomerization of an N -allylated tertiary amide in a macrocyclic setting. , Diene 5 was subjected to the same sequential RCM/isomerization conditions to afford ent - 2 , also in good yield (Scheme ). This RCM/isomerization could also be conducted in one pot with excellent yield (84%), as exemplified by conversion of 5 to ent - 2 (Scheme ).…”
mentioning
confidence: 99%
“…A very well-documented study in the synthesis of cyclohexane-fused 1,5-diazocin-6-one was reported by Fülöp and co-workers using a Pd(II)-catalyzed oxidative intramolecular cis -aminopalladation reaction [ 50 ]. Starting from tosyl-protected trans - N -allyl-2-aminocyclohexanecarboxamides 28 , the optimization of the reaction conditions allowed a highly regioselective formation of the medium-sized heterocycles 29 via an 8- endo -trig cyclization, with relatively good yields ( Scheme 13 ).…”
Section: Methods Using Palladium-catalyzed Reactionsmentioning
confidence: 99%